Handbook of Research Methods in Public Administration - EVAN M. BERMAN, JACK RABIN (Taylor & Francis Group, 2007)
The need for more rigorous and systematic research in public administration has grown as the complexity of problems in government and nonprofit organizations has increased. This book describes and explains the use of research methods that will strengthen the research efforts of those solving government and nonprofit problems. This book is aimed primarily at those studying research methods in masters and doctoral level courses in curricula that concern the public and nonprofit sector. Thus, students in programs in public administration, nonprofit management, criminal justice, nursing, and education, to mention a few, will be provided detailed information on conceptualizing, planning, and implementing research projects of many different types. The book is also aimed at consumers of research reports. For example, government executives who fund research must be able to determine whether the research objectives set out in the project are properly conceptualized and whether the research methods chosen are appropriate to the objectives and concepts. This volume will inform such research consumers. We would like to thank many anonymous peer reviewers for their critical reading of the chapters in this book. Other groups merit public attention. The first group has two members who served without anything but our thanks, and we thank them again in public—Professor Hindy L. Schachter, New Jersey Institute of Technology, and Professor Alfred Tat-Kei Ho, Indiana University-Purdue University Indianapolis. The second group is a group of methodologists who helped us by providing ideas for chapters, arguing with us about whether the quantitative–qualitative balance seemed right, and reviewing pieces of chapters or combinations of chapters or the entire manuscript. For these and the support of the book they represent, we thank you. The third group is comprised of the authors who appear here. Each of the authors worked incredibly hard to produce their best thinking and teaching ideas. All of them made suggestions about cross-indexing and ensuring that consistency was not forgotten. Many helped each other beyond what any editor could have asked. We thank each of you with enthusiasm.